Analisis Peranan Akuntansi Manajemen dalam Tren Biaya Produksi: Studi Kasus PT. Adhi Karya (Persero) Tbk - Naifah Amelia Ramadhani; Lutfatul Umamah; Indri Jihani; Salsa Oktavia Salbina (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study aims to analyze the role of management accounting in examining production cost trends, with the main focus of this study being to observe patterns of change in production costs, particularly in the components of direct raw material costs (DRMC), direct labor costs (DL), and factory overhead costs (FOC) at PT. Adhi Karya (Persero) Tbk and the extent to which the application of management accounting improves competitiveness, optimizes cost performance, increases operational efficiency, and improves the decision-making process. This study uses a descriptive qualitative approach using secondary data in the form of company financial reports, books, and relevant scientific articles. The analysis technique used is content analysis, and source triangulation is carried out to increase data validity. The results show that the management accounting system implemented by PT. Adhi Karya provides accurate cost information, enabling management to control production costs effectively. In addition, management accounting helps identify cost variables that affect fluctuations in production costs, as well as supporting budget planning and production performance evaluation. This study confirms that the optimal implementation of management accounting plays an important role in maintaining production cost stability and increasing the company's competitiveness. The conclusion of this study suggests that PT. Adhi Karya should continue to develop a management accounting system that is adaptive to changes in the business environment in order to face future production cost challenges.